Pathogenicity and Immune Responses of Aspergillus fumigatus Infection in Chickens - Cheng, Zhimin; Li, Mengxuan; Wang, Yao; Chai, Tongjie; Cai, Yumei; Li, Ning (Frontiers in Veterinary Science, 2020)
Aspergillus fumigatus is a ubiquitous pathogen in poultry farms, causing aspergillosis in chickens. To study the pathogenicity of Aspergillus fumigatus, 14-day-old chickens were infected with fungal conidia (2×107 CFU/mL) via thoracic intra-air sacs inoculation. The clinical symptoms, gross and histopathological lesions, and fungal load in the lungs were examined. Additionally, the mRNAs of Toll like receptors (TLR) and proinflammatory cytokines were evaluated by quantitative PCR to explore the immune responses induced by Aspergillus fumigatus. The results showed that overt depression, ruffled feathers, and dyspnea were observed in the infected chickens as early as 3 days post infection (dpi). Eleven out of 25 infected chickens died from 5 to 9 dpi, and Aspergillus fumigatus could also be reisolated from the infected lung. Histopathological examination revealed obvious airsacculitis and pneumonia, characterized by inflammatory cell infiltration (heterophils and macrophages), and granulomatous lesions in the lung. The mRNA expressions of TLR1 and TLR2 were upregulated in the lung and spleen, and most proinflammatory cytokines including IL-1, Cxcl-8, TNF-, IL-12, and IFN-γ were increased in both the lung and spleen during the tested period, suggesting that the innate immune responses were triggered by Aspergillus fumigatus infection, and these cytokines participated in the inflammatory responses against Aspergillus fumigatus. These results indicate that Aspergillus fumigatus infection by thoracic intra-air sacs inoculation can cause severe respiratory damage in chickens, activate TLR1 and TLR2 mediated immune responses, and elicit large expression of proinflammatory cytokines such as IL-1β, Cxcl-8 and IFN-. These data will help further understanding of the pathogenesis and immune responses of Aspergillus fumigatus infection in the chicken.